2013
DOI: 10.1002/0471142700.nc0301s53
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐Phase Supports for Oligonucleotide Synthesis

Abstract: This unit attempts to provide a reasonably complete inventory of over 280 solid supports available to oligonucleotide chemists for preparation of natural and 3'-modified oligonucleotides. Emphasis is placed on non-nucleosidic solid supports. The relationship between the structural features of linkers and their behavior in oligonucleotide synthesis and deprotection is discussed wherever the relevant observations are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 314 publications
(471 reference statements)
0
7
0
Order By: Relevance
“…The reduction of process-related impurities achieved using the CPG support 9 for solid-phase synthesis was measured for each DNA and RNA sequence, as described above for the DNA sequence 5 -d(TCTTGGTTACATGAAATCCT) and reported in the annotation to step 13 of Basic Protocol 6. Over the years, a plethora of solid supports has attracted attention in the context of oligonucleotide synthesis (see Current Protocols article: Guzaev, 2013). For example, the NittoPhase® solid support is a commercially available porous cross-linked polystyrene support with a high hydroxyl load and a pore size of ∼550 Å.…”
Section: Critical Parameters and Troubleshootingmentioning
confidence: 99%
“…The reduction of process-related impurities achieved using the CPG support 9 for solid-phase synthesis was measured for each DNA and RNA sequence, as described above for the DNA sequence 5 -d(TCTTGGTTACATGAAATCCT) and reported in the annotation to step 13 of Basic Protocol 6. Over the years, a plethora of solid supports has attracted attention in the context of oligonucleotide synthesis (see Current Protocols article: Guzaev, 2013). For example, the NittoPhase® solid support is a commercially available porous cross-linked polystyrene support with a high hydroxyl load and a pore size of ∼550 Å.…”
Section: Critical Parameters and Troubleshootingmentioning
confidence: 99%
“…Two types of a solid support are available; the most commonly used support, loaded support, has the first nucleoside attached to it, while a universal solid support is not pre‐loaded with nucleosides. Many different solid supports have been developed over the years (Guzaev, 2013). A loaded support and a commonly used universal support, UnyLinker™ (Guzaev & Manoharan, 2003; Ravikumar et al, 2008), are shown is Figure 2.…”
Section: Oligonucleotide Synthesis and Related Impuritiesmentioning
confidence: 99%
“…With this advanced technology, complex polypeptides and even some proteins can be chemically synthesized. [7,8] Originating from the synthesis of peptides, this simple and practical technology is expanded to the multistep synthesis of other complex bio-organic compounds, such as oligonucleotides [9][10][11] and oligosaccharides, [12][13][14][15] and makes a profound contribution in these fields. In addition, the solid-phase synthesis of small organic molecules has been rapidly developed since 1990s.…”
Section: Introductionmentioning
confidence: 99%